SENSORY PROPERTIES OF DAMBUN NAMA, FRIED AND PEPPER MEAT PRODUCTS PROCESSED FROM ISA BROWN LAYER CHICKENS - Musa, G. D.; Muhammad, A. S.; Kalla, D. J. U.; Jama’a, N. A. (Nigerian Journal of Agriculture and Agricultural Technology, 2024)
This study was conducted to evaluate the sensory properties of Isa brown Chicken Meat. Isa brown Layers were slaughtered, dressed and cut into pieces. The Meat was boiled and subjected to three processing methods namely Dambun Nama, Fried Meat and Pepper Meat using locally sourced ingredients and spices. A sample size thirty (30) staff and students of Abubakar Tafawa Balewa University, Bauchi were served the three meat products. Data were collected using a 9-point Hedonic scale on palatability, juiciness, tenderness, flavor, color, texture and acceptability. Results revealed that the best (P< 0.05) palatability value of 8.77 was obtained on the pepper meat, where as other parameters where not significantly affected by the different processing method. It was concluded that the three products were suitably and generally acceptable to the taste panelists, however, for long storage and long-distance travelers, Dumbun Nama is recommended due to its better shelf life.